2022
DOI: 10.1123/ijsc.2021-0099
|View full text |Cite
|
Sign up to set email alerts
|

Gender Representation at the 2018 Winter Olympic Games From an Australian Broadcast Perspective

Abstract: This study examined differences in the Seven Network’s primetime coverage of the 2018 PyeongChang Winter Olympic Games on all of its channels. Over 102 hr of total coverage was analyzed for clock time, name mentions, and the descriptions of athletes by announcers divided by gender. Results found that male athletes received the bulk of the clock time; 13 of the top 20 most-mentioned athletes were men. There were also gender differences in the word for word descriptors of success, failure, physicality, and perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…Thus, it remains to be seen whether the results of Xu et al’s study (2019) are a trend for the Australian coverage of a summer event or whether these were an outlier, as the results of the most-recent Winter Olympics (Scott et al, 2022) found that women only received 31.19% of the coverage. Results of Winter Games’ study mirror those of Toohey (1997) from the 1988 and 1992 Summer Olympic Games, who found that women accounted for 32.9% and 29.7% of the coverage.…”
Section: Literature Reviewmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, it remains to be seen whether the results of Xu et al’s study (2019) are a trend for the Australian coverage of a summer event or whether these were an outlier, as the results of the most-recent Winter Olympics (Scott et al, 2022) found that women only received 31.19% of the coverage. Results of Winter Games’ study mirror those of Toohey (1997) from the 1988 and 1992 Summer Olympic Games, who found that women accounted for 32.9% and 29.7% of the coverage.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Results of their work suggested that American women athletes were being covered more because of their medal winning success for their home nation, which draws in viewers to see the success of their nation at a globally important event (Billings & Angelini). Over a long period in the Australian media context of the Olympic Games coverage, women athletes received far less coverage than male athletes no matter the media platform that was analyzed (Eagleman et al, 2014; Jones, 2013; Lumby et al, 2014; Scott & Kunkel, 2016; Scott et al, 2022; Stoddart, 1994; Toohey, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations